Covid-19 – A Call for Socio-Economic Policy Implementation and People’s Socio-Economic Behavior Change in Uganda - Tebitendwa, Antony (Archives of Business Research, 2021)
The outbreak of COVID-19 has called for proper policy implementation on the side of the government of Uganda. Uganda has a policy on food and nutrition that is responsible for maintaining food reserves (or funds to be used for staple food purchase) at household, sub-county, district, regional and national levels, to boost disaster preparedness. But this and many other policies that are intended to support socio-economic lives have never been fully implemented. The government has also been called upon to strengthen financial institutions to encourage people to save. Ugandans too, are encouraged to embrace the culture of saving. Therefore, COVID-19 lockdown has awakened Ugandans to change their spending behavior given the uncertain future. Besides, the pandemic has also checked on Uganda’s socio-cultural behavior, calling for a change in terms of greeting gestures and personal space, religious beliefs, land ownership, hygiene, and educational accessibility.